Perceptions on shariah governance framework of Islamic banking in Oman: issues and challenges = تصورات حول إطار الحوكمة الشرعية للصيرفة الإسلامية في عمان: قضايا وتحديات - Alnofi, Abdulrahman; Engku Ali, Engku Rabiah Adawiah (IIUM Press, International Islamic University Malaysia, 2019)
Oman has adopted the Sharī’ah governance framework which is very similar to other countries that face issues of Sharī’ah governance such as independence, competency, and disclosure. Therefore, this study will examine these main issues in the Sharī’ah governance framework of Oman. This paper aims to examine the current practice of Sharī’ah governance in Oman from the perspectives of Sharī’ah advisors, bankers and regulators. The paper focuses on the present practice of Sharī’ah governance framework and related issues such as independence, competency, and disclosure. The paper uses the descriptive research method in terms of collecting secondary data and information for the literature review. Since the availability of data and information on Sharī’ah governance practices in Oman is very limited, a semi-structured interview was conducted with Sharī’ah advisors, officers and regulators to explore their perceptions on Sharī’ah governance and related issues. The findings of the paper reveal that the regulators have put in place an excellent Sharī’ah governance framework and it may be considered as one of the best frameworks in the Islamic banking industry. However, there are shortcomings and weaknesses in the current practice of Sharī’ah governance frameworks, such as lack of experience, lack of research in the field of Islamic banking and finance and low position of internal Sharī’ah review. This study provides and proposes some recommendations for enhancing the present Sharī’ah governance framework. ****************************************************************************** تتبنى عمان نظاما للحوكمة الشرعية شبيها لنظام الحوكمة في بعض الدول التي تواجه بعض المشكلات التي تتمثل في الاستقلالية والشفافية والكفاءة مما يجعل احتمال أن تتكرر هذه المشكلات في عمان. هدفت الدراسة إلى بحث وتقصي إطار الحوكمة الشرعية الحالي في عمان من منظور الم نظمين وأعضاء اللجان الشرعية وبعض موظفي البنوك الإسلامية. كما ركزت الدراسة أيضا على الممارسة الحالية للحوكمة الشرعية في عمان وبعض قضاياها ا لأساسية مثل الاستقلالية والكفاءة والشفافية. استخدمت الدراسة أسلوب البحث الوصفي من حيث جمع البيانات والمعلومات الثانوي ة في الدراسات السابقة، ونظرا لقلة الدراسات في هذا الموضوع تم استخدام أسلوب المقابلة شبه المنظمة مع أعضاء اللجان الشرعية والمنظمين وبعض موظفي البنوك لدراسة نظرت م حول نظام الحوكمة الشرعية في عمان. نتيجة الدراسة أظهرت أن إطار الحوكمة الشرعية للبنوك الإسلامية في عمان يمكن أن يكون واحدا من أفضل الأطر والأنظمة في صناعة المالية الإسلامية الحالية، إلا أن هناك بعض نقاط الضعف والنقص بحاجة إلى المعالجة مثل نقص الخبرة ونقص الدراسات في مجال ال بنوك الإسلامية والمالية في عمان وضعف مكانة المراجع الشرعي، وفي النهاية أوصت ا لدراسة القائمين والممارسين لنظام الحوكة الشرعية في عمان الأخذ بنتيجة وتوصيات الدراسة لتحسين نظام الحوكمة الحالي